Information System for Drug Sales at Advent Hospital Medan - Hutahaean, Mian Natanael; Singarimbun, Roy Nuary; Purwawijaya, Ellanda (Journal of Technology and Computer, 2025)
The management of drug sales data in hospitals plays a crucial role in ensuring operational efficiency and patient safety. However, the semi-manual process at Advent Hospital Pharmacy in Medan often leads to issues such as stock data inaccuracies and reporting delays, with a transaction error rate reaching 20%. This study aims to design and build a desktop-based drug sales information system using Microsoft Visual Basic.net to address these problems. The development method used is Research and Development (R&D) with a waterfall model, which includes the stages of requirements analysis, design, implementation, and testing. The system was evaluated through two approaches: a usability test with a questionnaire administered to 5 users and a black-box test with 13 functional scenarios. The results showed that the developed system achieved a usability score of 81%, which falls into the "Good" category. Meanwhile, the black-box test results indicated a system effectiveness rate of 85%, with 11 out of 13 test scenarios being successful. This system has been proven to improve data accuracy and sales process efficiency, although further improvements are needed for the input validation and report printing features.